2019
DOI: 10.3389/fpubh.2019.00099
|View full text |Cite
|
Sign up to set email alerts
|

The New Runner's High? Examining Relationships Between Cannabis Use and Exercise Behavior in States With Legalized Cannabis

Abstract: Scientific literature examining cannabis use in the context of health behaviors, such as exercise engagement, is extremely sparse and has yielded inconsistent findings. This issue is becoming increasingly relevant as cannabis legalization continues, a situation that has been associated with increased initiation of use among adults, and increased potency of available products in legalized states. Physical activity is among the most important health behaviors, but many Americans do not meet minimum exercise reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 20 publications
2
23
3
Order By: Relevance
“…Cannabis use concurrently with exercise was lower in this sample than the 81.7% found in a previous report, and unlike that study we did not find a difference by sex (data not shown); however, we did corroborate the finding that younger adults tended to use cannabis before and after exercise more often than older adults (YorkWilliams et al 2019). In the previous study, the main reasons for cannabis use concurrent with exercise were enhanced performance, enjoyment, motivation, and recovery.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Cannabis use concurrently with exercise was lower in this sample than the 81.7% found in a previous report, and unlike that study we did not find a difference by sex (data not shown); however, we did corroborate the finding that younger adults tended to use cannabis before and after exercise more often than older adults (YorkWilliams et al 2019). In the previous study, the main reasons for cannabis use concurrent with exercise were enhanced performance, enjoyment, motivation, and recovery.…”
Section: Discussioncontrasting
confidence: 55%
“…Historically, cannabis use in athletes has typically been studied in the framework of abuse among adolescent, university, and elite athletes (Ware et al 2018;Buckman et al 2011;Peretti-Watel et al 2003a). More recent studies have suggested that athletes are using cannabis to improve mood and enjoyment of exercise (YorkWilliams et al 2019), but patterns of use and positive and adverse effects to cannabis in adult athletes is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Research also suggests that cannabis may have positive effects on improving both self‐reported sleep quality and non‐rapid eye movement sleep (Lee et al., 2018; Mondino et al., 2019). Reviews suggested that cannabis users are more likely to engage in physical activities and experience enhanced recovery after exercise (YorkWilliams et al., 2019). There is also a possible link between cannabis use and improvement in psychological symptoms such as anxiety and depression in cancer patients, but the results are inconclusive (Whiting et al., 2015; Zhang et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Acute cannabis consumption may reduce exercise pain and thus increase endurance (Huestis et al 2011), but chronic use does not. In survey research, most people using cannabis with exercise reported reduced pain and/ or increased their enjoyment of the exercise activity (Lisano et al 2019a;YorkWilliams et al 2019;Zeiger et al 2019).…”
Section: Summary Of Resultsmentioning
confidence: 99%